A Review of 2016–2017 Agricultural Youth Injuries Involving Skid Steers and a Call for Intervention and Translational Research. Issue 4 (2nd October 2018) - Weichelt, Bryan; Bendixsen, Casper
ABSTRACT: Skid steers or loaders are becoming prolific in U.S. agriculture – as are the injuries and fatalities related to their use. A review of incidents as queried in AgInjuryNews from 2016 to 2017 revealed an overrepresentation of youth being involved in these tragic incidents. This raises concerns over parental attitudes and beliefs about the safety of these machines. Skid steer incidents do not appear to be a result from a lack of safety education materials, however. Indeed, manufacturers, the Centers for Disease Control, and many state extension systems have safety manuals and general instruction, including YouTube videos and online resources. Thus, there appears to be a significant gap between safety knowledge and practice. There is also a lack of published research, including intervention strategies, training evaluation, and translational/implementation studies specific to skid steer machines. This review of youth incidents is therefore also a call for further research for foundational studies regarding attitudes and behaviors involving skid steers in agriculture, intervention models, and efforts to translate prevention knowledge beyond the existing materials.